1976
DOI: 10.1177/030098587601300108
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Experimental Rocky Mountain Spotted Fever in Rhesus Monkeys

Abstract: Abstract. Rhesus monkeys were inoculated intravenously or intraperitoneally with various numbers of Rickettsia rickettsii. Monkeys that were given more than lo4 organisms intravenously died on days 3-6 after inoculation, whereas those given less than los intravenously or more than lo4 intraperitoneally died on day 7 or later. There was no significant difference in incidence of lesions between the early-and late-death groups. Vasculitis and thrombosis occurred most frequently in the nares, pinna of the ear, scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1976
1976
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In another experimentally induced RMSF infection of dogs, the testicles were one of the most notable sites of microscopic lesions 4 . Experimental infection of rhesus monkeys led to coagulation necrosis of the seminiferous tubules and parenchyma of the testicle and epididymis with necrotic areas generally located adjacent to thrombosed blood vessels 5 . In that study, indirect immunofluorescence microscopy identified rickettsiae in the testicles, and relatively high counts of viable rickettsiae were recovered from the testes as well 5 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In another experimentally induced RMSF infection of dogs, the testicles were one of the most notable sites of microscopic lesions 4 . Experimental infection of rhesus monkeys led to coagulation necrosis of the seminiferous tubules and parenchyma of the testicle and epididymis with necrotic areas generally located adjacent to thrombosed blood vessels 5 . In that study, indirect immunofluorescence microscopy identified rickettsiae in the testicles, and relatively high counts of viable rickettsiae were recovered from the testes as well 5 .…”
Section: Discussionmentioning
confidence: 85%
“…Although orchitis is reported as an experimental sequela of RMSF, 3–5 there are no reports that describe orchitis and epididymitis as a predominant feature of natural disease in dogs. Because many dogs receiving routine veterinary care are neutered at a young age, there is a paucity of information regarding the involvement of the testicles in dogs with RMSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccinated guinea pigs challenged by the subcutaneous (s.c.) route or by aerosol were fully protected. RMSF infection has been studied extensively in rhesus monkeys (7,9,12,15), and a suitable nonhuman primate model has been described (10). The vaccine has been tested and found to protect rhesus monkeys challenged s.c. (11).…”
mentioning
confidence: 99%